2009
DOI: 10.1093/hmg/ddp115
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic retention of polyglutamine-expanded androgen receptor ameliorates disease via autophagy in a mouse model of spinal and bulbar muscular atrophy

Abstract: The nucleus is the primary site of protein aggregation in many polyglutamine diseases, suggesting a central role in pathogenesis. In SBMA, the nucleus is further implicated by the critical role for disease of androgens, which promote the nuclear translocation of the mutant androgen receptor (AR). To clarify the importance of the nucleus in SBMA, we genetically manipulated the nuclear localization signal of the polyglutamine-expanded AR. Transgenic mice expressing this mutant AR displayed inefficient nuclear tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
146
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(160 citation statements)
references
References 71 publications
12
146
2
Order By: Relevance
“…Furthermore, although the processing route was not investigated, the tumor antigen CDC27 is better presented to CD4 + T cells when located in the cytoplasm rather than the nucleus (24). In addition, two polyglutamine-expanded proteins involved in the pathogenesis of neurologic disease, ataxin-5 (25) and androgen receptor (26), resist degradation by autophagy in the nucleus but not the cytoplasm. Such findings are consistent with autophagy being predominantly a cytoplasmic process, with autophagosomes mainly forming in the cell periphery far away from the nucleus (21).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, although the processing route was not investigated, the tumor antigen CDC27 is better presented to CD4 + T cells when located in the cytoplasm rather than the nucleus (24). In addition, two polyglutamine-expanded proteins involved in the pathogenesis of neurologic disease, ataxin-5 (25) and androgen receptor (26), resist degradation by autophagy in the nucleus but not the cytoplasm. Such findings are consistent with autophagy being predominantly a cytoplasmic process, with autophagosomes mainly forming in the cell periphery far away from the nucleus (21).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, observations that expression of a truncated AR results in substantially greater toxicity (18,31,41) than does expression of the fulllength expanded polyglutamine protein (7,11,29) suggested that proteolysis of the polyglutamine-expanded AR produces a toxic and aggregation-prone fragment. We therefore sought to explore the mechanism and timing of AR cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence-PC12 cells, primary neuronal cultures, and mouse tissue sections were fixed and stained as described previously (11). Antibodies used included AR(H280) (1:100), AR(441) (1:50) (Santa Cruz Biotechnology), 3B5H10 (1:4000) (a kind gift from Steve Finkbeiner, Gladstone Institute of Neurological Disease), anti-FLAG antibody (1:100) (Pierce), and SMI32 (1:1000) (Sternberger Monoclonals Inc., Baltimore, MD).…”
Section: Construction Of Double Labeled Expanded Polyglutamine Ar (Dmentioning
confidence: 99%
See 2 more Smart Citations